(untitled) (Journal of Asian Development Studies, 2023)
The research study was conducted in the Dir Forest Division of the KP Forest Department. The primary purpose was to estimate the socioeconomic values of ecosystem services of forests. For this study, 120 respondents were selected in 10 villages of the Dir Forest division through random sampling techniques. The study showed that firewood is the primary fuel source, and the local communities procured huge amounts of firewood from plantations and farmlands through local purchases. The economic value of forest ecosystem regulation, support, and cultural services must be addressed at the public level. As a result, the overall worth of the forestry industry in the globe in general, and Pakistan in particular, could be considered much higher. This study aimed to determine the relevance of various types of ecosystem services and their relationship to the socioeconomic status of individuals in the Dir Forest division. It focuses on estimating the economic value of a subset of services relevant to local communities, such as provisioning services (fuel wood) and cultural services (tourism), using the stated preference method (Contingent Valuation) and recommending a feasible payment for ecosystem services (PES) mechanism. According to data from the Economic valuation of fuel wood services, Dir Forest Division obtains a total of US 04 million- USD worth of fuel wood services per year. To determine the tourism trend and its economic worth, data was collected from hotel owners, 120 tourists, and key informants in the study area using a pretested questionnaire for seven years, from 2015 to 2021.